Gendered Peace: Four Hungarian Women Writers Against the Two World Wars. (2nd July 2017) - Farkas, Ákos
ABSTRACT: Hungary's leading women writers from Margit Kaffka to Piroska Szenes took passionate sides when compelled to choose between the 'maternal' protection of life and the patriot's loyalty to 'fatherland'. 'If only … this whole wartime world was turned upside down!' and 'No peace on earth before the last bit of soil … is regained!' were characteristic wishes made by women writers on either side of the pacifist versus patriot divide. The article seeks to answer the question what, beyond background and temperament, motivated the emblematic female figures of Hungary's interwar literature coming out in favour of peace, country, or both.